Raters and examinees training for objective structured clinical examination: comparing the effectiveness of three instructional methodologies - Jefferson Garcia Guerrero; Ayidah Sanad Alqarni; Lorraine Turiano Estadilla; Lizy Sonia Benjamin; Vanitha Innocent Rani (BMC, 2024)
Abstract Background Utilizing the objective structured clinical examination (OSCE) ensures objectivity when it comes to the assessment of nursing students' skills and competency. However, one challenge in OSCE integration is rater and examinee training and orientation. Aim This study employed a quasi-experimental design to evaluate the effectiveness of different instructional methodologies in training and preparing raters and examinees for the OSCE. Methods Participants were divided into three group of training methodologies: online, simulation, and traditional lecture (six raters and 18 examinees were assigned to each group). A total of 18 raters and 54 examinees partook. Results The study found that raters trained through simulation exhibited a slight agreement with their rates, compared to those who were trained online and in traditional lectures. Moreover, examinees who were trained through the simulation methodology performed better compared to those trained via the other methodologies. Conclusions The study findings indicate that using simulation by training raters and examinees in the OSCE is the most effective approach.